Dowry, the Oppression of Women and Femicide in Bangladesh (Journal of Comparative Social Work, 2018)
The marriage transaction, commonly known as dowry, is a widespread phenomenon in Bangladesh, which has inevitably attracted much attention from social science researchers. This has transformed bride wealth marriages to dowry marriages in Bangladeshi society. A dowry is what the groom’s side demands in cash and kind from the bride’s side to complete the marriage. It is a major cause of women’s oppression, which starts from diversified psychological and physical torture that finally turns into femicide. The main objective of this paper is to analyse women’s oppression because of the dowry practice through marriage as a social problem in Bangladesh. This paper also explains the various dimensions of this problem, its multiple functions in women’s oppression, the nature of oppression in its various stages before femicide and the nature of femicide. The paper draws on secondary data from Bangladesh. It is observed that women in Bangladesh are physically, psychologically and socially oppressed by their husband and his family members in many ways because of the dowry. The nature of oppression is diverse in form, but ultimately these oppressions turn into femicide. The nature of femicide is also diverse, and some fire-related deaths and the suicides of young married women are also believed to be related to dowry.